Agent-based service discovery in ad-hoc communications environments - Lu, Ying (University of Ottawa (Canada), 2004)
Service Discovery allows for the automatic and spontaneous discovery and configuration of network services. It is especially important in ad-hoc environments where the network topology is unpredictable. We propose the use of Agent Technology, an efficient and convenient technology, in our work to shed new light in this area. Our first model takes on a centralized architecture. One agent in the network, the Service Discovery Agent (SDA), assumes the responsibility of maintaining the central service repository. Each service and user has their own agents which we name Service Agents (SAs) and Personal Agents (PAs) respectively. SAs are responsible for registering and deregistering their services with the SDA. Our second discovery model uses a distributed architecture that can operate in a fully dynamic environment. For this we use an existing probabilistic P2P search algorithm as a basis. Discovery is performed on demand using the concepts of the P2P search algorithm. The algorithm is enhanced in many ways so that it is adapted to an ad-hoc environment while still keeping the basic efficient operations. As more searches are performed, devices become more knowledgeable and discovery performance would improve. (Abstract shortened by UMI.)
Keywords: Computer Science.